Familial hipercholesterolemia – pathogenesis, clinic and management - Kłosiewicz-Latoszek, Longina; Cybulska, Barbara (Przewodnik Lekarza/Guide for GPs, 2006)
Familial hypercholesterolemia (FH) is a genetic disorder, which occurs in two forms, as homozygous FH with frequency 1/1 000 000 persons or heterozygous FH with frequency 1/500 persons, what makes about 78 000 cases in Poland. The lack of LDL receptors or deficiency of half of LDL receptors, due to various mutations of genes encoding the proteins of these receptors, is responsible for homozygous FH or heterozygous FH respectively. Familial FH is a very strong risk factor for premature CHD. The diagnosis of this disorder is based on high LDL cholesterol level in the patient and his close relatives. Additionally xanthomata, particularly of tendon, are present in some cases. Strong statins are drugs of choice for heterozygous FH treatment. Atorvastatin in a daily dose of 80 mg and rosuvastatin (not registered in Poland) are particularly recommended. In future the combination therapy with statins and ezetimibe (still not available in Poland) may be an option. LDL-apheresis at 1 to 2 weekly intervals is the best method of treatment of homozygous FH. For all the time patients should be treated with a strong statin.